A Model for Creating Business Competitiveness Based on Technosociopreneur Innovation Characterized by State Defense Values - Erna Sulistyowati; Rida Perwita Sari; Rika Puspita Sari (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: MSMEs in Surabaya are adapting to global economic challenges like unemployment and poverty through a technosociopreneurial approach, integrating digital technology with social motives and national defense values. This adaptation aims to enhance competitiveness and ensure sustainability during the new normal. The research focuses on a competitiveness model based on technosociopreneur innovation while addressing challenges like rising unemployment, requiring MSMEs to prioritize societal benefits over profit and embrace digital tools for success.Methodology: This research uses a mixed method approach which is an approach in research that combines or connects qualitative and quantitative research methods (including philosophical foundations, using approaches and combining both approaches in research). Finding: Technosociopreneurs have a significant role in dealing with technological changes and increasingly fierce business competition. They can combine technological and social elements to create innovations that positively affect business and society. The success of technosociopreneurs can positively impact achieving higher competitiveness in today's digital era.Conclusion IT-based product innovation affects competitiveness mediated by technosociopreneur IT-based process innovation has an effect on competitiveness mediated by technosociopreneur. IT-based organizational innovation affects competitiveness mediated by technosociopreneur 7.